2012
DOI: 10.1593/neo.12444
|View full text |Cite
|
Sign up to set email alerts
|

Statins Impair Glucose Uptake in Tumor Cells

Abstract: Statins, HMG-CoA reductase inhibitors, are used in the prevention and treatment of cardiovascular diseases owing to their lipid-lowering effects. Previous studies revealed that, by modulating membrane cholesterol content, statins could induce conformational changes in cluster of differentiation 20 (CD20) tetraspanin. The aim of the presented study was to investigate the influence of statins on glucose transporter 1 (GLUT1)-mediated glucose uptake in tumor cells. We observed a significant concentration- and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 48 publications
1
43
0
1
Order By: Relevance
“…9 The emergence of statins as effective cholesterol-lowering agents during hypercholesterolemia also brings with it anticancer benefits beyond cardiovascular protection. The findings of Malenda et al 8 reported in Neoplasia reveal the effect of statins on glucose metabolism of tumor cells. Although earlier reports have indicated that statins can promote apoptosis or, arrest proliferation in cancer cells; in this report the investigators demonstrate using sound methodology that pre-incubation of tumor cells with statins impair glucose uptake.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…9 The emergence of statins as effective cholesterol-lowering agents during hypercholesterolemia also brings with it anticancer benefits beyond cardiovascular protection. The findings of Malenda et al 8 reported in Neoplasia reveal the effect of statins on glucose metabolism of tumor cells. Although earlier reports have indicated that statins can promote apoptosis or, arrest proliferation in cancer cells; in this report the investigators demonstrate using sound methodology that pre-incubation of tumor cells with statins impair glucose uptake.…”
mentioning
confidence: 87%
“…Conversely, a prolonged blockade of glucose uptake would necessitate the cells to curtail or temporarily arrest all major energy-dependent synthetic and secretory activities, ultimately leading to cell death. Since Malenda et al, 8 haven't observed any cell death it is likely the cells are under transient metabolic arrest. Such an arrest in protein synthesis or translation could be assessed by several approaches, such as 35 S-methionine incorporation.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…In tumor cells, the expression of the glucose transporter, GLUT-1, is frequently upregulated, as tumor cells require a high glucose supply for their increased metabolic demands. Studies using statins performed on human Burkitt lymphoma, human follicular lymphoma, and human colon adenocarcinoma have shown that statins are not able to inhibit expression of GLUT proteins, but by inhibition of cholesterol synthesis, they could induce conformational changes in GLUT proteins that possess multiple membrane-spanning domains [59]. It was previously shown that cholesterol can associate with a number of membrane proteins via covalent or noncovalent interactions and also induces condensation of membrane lipids and formation of membrane rafts.…”
Section: Hydrophobic Vs Hydrophilic Statinsmentioning
confidence: 99%
“…In lymphoma, statins were recently shown to induce apoptosis by promoting ROS generation and Akt, Erk and p38 signalling pathway regulation . Malenda et al also demonstrated that HMG‐CoA reductase inhibitors impair glucose uptake in tumor cells possibly by inhibiting a putative cholesterol‐binding motif in the juxtamembrane fragment of glucose transporter 1 (GLUT‐1) .…”
Section: Discussionmentioning
confidence: 99%